A Case Of Oral Lichen Planus Associated With Desquamative Gingivitis With Periodontitis - Cheah Chia Wei; RathnaDevi Vaithilingam; Siar Chong Huat; Norazlina Mohammad (Faculty of Dentistry, University of Malaya, 2024)
Volume :26 No :5 (page: 30-33)